Virulence genes of Vibrio parahaemolyticus isolated from acute hepatopancreatic necrosis disease associated with shrimp and grow-out pond water - Chonsin, Kaknokrat; Siriphap, Achiraya; Changkaew, Kanjana; Noisumdaeng, Pirom; Suthienkul, Orasa (Journal of Medicine and Health Sciences, 2021)
Vibrio parahaemolyticus, a marine bacterium, is an etiologic agent of acute gastroenteritis disease outbreaks among people worldwide. A newly emerged V. parahaemolyticus caused acute hepatopancreatic necrosis disease (AHPND) among cultivated shrimp occurred in 2010. The AHPND outbreak caused major shrimp industry losses in many countries. The V. parahaemolyticus strain carried toxin genes (i.e., pirA and pirB) on its plasmid is pathogenic to shrimp. This study investigated the presence of human pathogenic genes, tdh and trh, and shrimp pathogenic genes, pirA and pirB, from AHPND related samples. A preserved stock culture of 83 V. parahaemolyticus were isolated from the AHPND affected white shrimp (n=28) and grow-out pond water (n=55) were examined. The tested strains were originally isolated from white shrimp and rearing pond water samples of one single private farm located in Eastern Thailand during the AHPND outbreak in 2013. The individual isolates were tested using the genotyping method by multiplex PCR. The results revealed that all 83 (100%) V. parahaemolyticus isolates were lacking human pathogenic virulence genes (tdh-trh-). When examined using the virulence markers of the AHPND causing strain, 74 (74/83, 89.16%) isolates were pirA-pirB- strains and nine (9/83, 10.84%) isolates (two [2/28, 7.14%] white shrimp and seven [7/55, 12.73%] grow-out pond water isolates) were pirA+pirB+ strains. This finding showed that V. parahaemolyticus with AHPND-associated genes presented in both shrimp and grow-out pond water. Consequently, probing the virulence genes of newly emerged V. parahaemolyticus strains would be essential for epidemiological surveillance and environmental monitoring.